PECULIAR FEATURES OF THE PRINCIPLE OF SEPARATION OF POWERS IN THE REPUBLIC OF UZBEKISTAN: THEORETICAL AND LEGAL FOUNDATIONS - Azizov Latifjon Kalandarovich (Modern American Journals, 2026)
The principle of separation of powers constitutes one of the fundamental pillars of modern constitutionalism and democratic governance. It is traditionally associated with the division of state authority into legislative, executive, and judicial branches, each functioning independently while maintaining a system of mutual checks and balances. In the Republic of Uzbekistan, the principle of separation of powers has undergone a distinctive process of formation and development shaped by historical experience, national legal traditions, and the country’s gradual transition toward a democratic state governed by the rule of law.This article explores the theoretical and legal foundations of the principle of separation of powers in Uzbekistan, emphasizing its specific features and national characteristics. The study analyzes the constitutional basis of the principle, its implementation within the system of state authorities, and the interaction between branches of power in the Uzbek model of governance. Particular attention is paid to the role of constitutional reforms, institutional evolution, and legal mechanisms that ensure balance and cooperation among state bodies. The research demonstrates that the Uzbek approach to the separation of powers represents a unique synthesis of classical constitutional theory and national state-building priorities.
Keywords: Separation of powers, constitutionalism, state authority, checks and balances, legislative power, executive power, judicial power, Republic of Uzbekistan, constitutional reforms, rule of law.